MSC Secretome's Antibacterial Activity on P. aeruginosa Isolated from Diabetic Ulcer Patient - Dini Assyfa; Marlina Marlina; Akmal Djamaan (LPPM Universitas Abdurrab, 2024)
The study aims to determine the antibacterial activity of adipose tissue-derived Mesenchymal Stem Cell (MSC) secretome against P. aeruginosa bacteria isolated from diabetic ulcer patients. Bacteria were isolated from specimens obtained from diabetic ulcer patient and identified using MacConkey and Blood Agar media followed by Polymerase Chain Reaction (PCR) molecular identification. Confirmed P. aeruginosa bacteria were used to evaluate the MSC secretome's antibacterial activity via the Kirby-Bauer method. Isolated bacteria grew on MacConkey media as gram-negative, non-lactose-fermenting bacteria, showing hemolytic capabilities on Blood Agar media. PCR identification yielded positive results for P. aeruginosa. In antibacterial activity testing against isolated bacteria, MSC secretome at concentrations of 1.25%, 2.5%, 5%, and 10% exhibited efficacy with average inhibitory zones measuring 8.17 mm, 8.23 mm, 8.52 mm, and 9.30 mm, respectively. The MSC secretome demonstrates antibacterial activity against P. aeruginosa bacteria isolated from diabetic ulcer patients.